Clinical Efficacy and Nephrotoxicity of the Loading Dose Colistin for the Treatment of Carbapenem-Resistant Acinetobacter baumannii in Critically Ill Patients - Wasan Katip; Suriyon Uitrakul; Peninnah Oberdorfer (MDPI AG, 2021)
Carbapenem-resistant Acinetobacter baumannii (CRAB) is one of the most common causes of nosocomial infections in critically ill patients. Colistin methanesulfonate (CMS), an inactive prodrug, has been considered as a last-resort treatment for CRAB infection in critically ill patients. The objective of this study was to assess 30-day survival and nephrotoxicity in critically ill patients who received non-loading dose (LD) versus LD of CMS for CRAB infection treatment. Between 2012 and 2017, this retrospective cohort analysis was performed at Chiang Mai University Hospital (CMUH), focusing on critically ill patients with CRAB infection who received either non-LD or LD of CMS. A total of 383 patients met the criteria for inclusion. At the 30th day of treatment, the survival rate of patients in the LD CMS group was 1.70 times (adjusted HR) of those in the non-LD group (95% CI = 1.17-2.50, p = 0.006). Clinical response was significantly higher in the LD CMS group than non-LD CMS group (aHR, 1.35, 95% CI, 1.01-1.82, p = 0.046). In addition, a microbiological response-eradication of pre-treatment isolated pathogens in post-treatment cultures-in patients with LD CMS was 1.57 times that of patients with non-LD CMS (95% CI, 1.15-2.15, p = 0.004). Additionally, there was a significant difference in nephrotoxicity between LD CMS and non-LD CMS (aHR, 1.57, 95% CI, 1.14-2.17, p = 0.006). Based on these results, LD CMS should be used to increase the opportunity of patients to achieve favourable outcomes. However, LD CMS was found associated with an increase in nephrotoxicity, so renal function should be closely monitored when LD colistin was administered.